ANALYSIS OF KEDIRI CITY’S FISCAL DEPENDENCY ON CENTRAL GOVERNMENT TRANSFER FUNDS AND ITS IMPACT ON REGIONAL INDEPENDENCE IN THE ERA OF DECENTRALIZATION - Ezra Stevanus Aloo; Eva Hany Fanida; Revienda Anita Fitrie (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the level of fiscal dependency of the Kediri City Government on central government transfer funds and its implications for regional financial independence within the framework of fiscal decentralization. The study employs a quantitative descriptive approach supported by a literature review to strengthen the theoretical foundation. The data used are secondary data in the form of the realization of the Regional Revenue and Expenditure Budget (APBD) of Kediri City for the period 2021–2025, obtained from the Satu Data Kediri portal and official publications of the Central Bureau of Statistics. The analysis is conducted using the regional financial independence ratio, which is the comparison between local own-source revenue (PAD) and transfer revenue as the main indicator in measuring regional fiscal capacity. The results show that the fiscal independence ratio of Kediri City ranges from 28.16% to 42.27%, indicating that the level of fiscal independence remains relatively low and falls within the instructive relationship category. This condition reflects a high dependence on central government transfers. However, the Human Development Index (HDI) of Kediri City shows a consistent upward trend, suggesting that transfer funds continue to play a significant role in supporting regional development, particularly in strategic sectors.